Comparison between Brainstorming and Presentation Teaching-Learning Methods in School of Nursing Rajanpur Punjab Pakistan - Asma Nazir (Babali Health, 2021)
Introduction: It is necessary to identify the students' diversities when we are going to perform our teaching in the classroom, it is also essential when we prepare our lecture to conduct in the classroom. Teachers used various methods to teach the students in the classroom. Several earlier studies are available on the effectiveness of different models of teaching approaches. This study intended the effect of using brainstorming and presentation teaching-learning strategies. Methods: Exploratory study design was used. 42 female nursing students of 2nd year class from 4-year diploma of general nursing and eight professional nursing instructors of School of Nursing Rajanpur. Descriptive statistics were used to identify the effectiveness of elected (brainstorming & presentation) teaching-learning strategies. Chi square was used to compare the academic performance (marks obtained) between students having different teaching-learning style. Results: The result showed that mean and standard deviation score for brainstorming and presentation teaching-learning strategies were 10.16±1.51 and 10.97±1.27. There is significant difference between group categories (<.05). Conclusion: The findings from this study show that presentation teaching-learning method plays a notable effect on students learning. This study as well exemplify that different teaching-learning method with advance technology is more useful than the conventional methods of teaching-learning.